2007
DOI: 10.1002/gj.1083
|View full text |Cite
|
Sign up to set email alerts
|

Major events of Paleogene mammal radiation in China

Abstract: On the basis of mammalian biostratigraphical study, the Paleogene was subdivided into 11 land mammal ages in China: the Paleocene Shanghuan, Nongshanian and Gashatan; the Eocene Lingchan, Arshantan, Irdinmanhan, Sharamurunian, Naduan and Ulangochuan; and the Oligocene Ulantatalian and Tabenbulukian. Biostratigraphical correlation with North American Land Mammal Ages, plus some palaeomagnetic, isotopic and radiometric results, established the indirect connection with the international time scale. Under this bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…207,209 We collect animals' data to construct fauna evolution during the Cenozoic (Figure 8; Supplementary data). [240][241][242][243][244][245][246] The fauna shows a great variability along with palaeoclimate changes in middle latitude Asia, which can also be roughly divided into three stages. In the Eocene, the composition of mammalian faunas has changed dramatically (Figure 8).…”
Section: Asian Flora and Fauna Evolution During The Cenozoicmentioning
confidence: 99%
“…207,209 We collect animals' data to construct fauna evolution during the Cenozoic (Figure 8; Supplementary data). [240][241][242][243][244][245][246] The fauna shows a great variability along with palaeoclimate changes in middle latitude Asia, which can also be roughly divided into three stages. In the Eocene, the composition of mammalian faunas has changed dramatically (Figure 8).…”
Section: Asian Flora and Fauna Evolution During The Cenozoicmentioning
confidence: 99%
“…In Eurasia, climate cooling at the Eocene-Oligocene boundary is associated with a major faunal turnover called "Grande Coupure", during which 60% of endemic European fauna (82% of placental mammals) went extinct; subtropical taxa declined and new taxa (e.g., rhinoceroses) migrated from Asia. The vertebrate records from Mongolia also show a strong turnover with Perissodactyla replaced by lagomorphs and rodents (Yuanqing et al, 2007), consistent with a trend to aridification indicated by the lithology (Dupont-Nivet et al, 2007;Kraatz & Geisler, 2010) and by changes in rodent dental patterns (Gomes Rodrigues et al, 2012).…”
mentioning
confidence: 64%
“…Prior to the flourishing of the Paleocene archaic mammals (Alroy, 1998;Yuanqing et al, 2007), some of which attained very large body sizes (Alroy, 1998;Alroy et al, 2000), the earliest Paleocene mammals were de facto small-bodied forest dwellers. Small body sizes were retained by macroscelids into the Eocene, as discussed for C. kasserinensis.…”
Section: Research Articlementioning
confidence: 99%